Aplikasi Mobile Pemetaan Pengunjung Museum Trowulan Berbasis Bluetooth Indoor Positioning System Menggunakan Metode Trilateration - Jonathan Kurnia Anggita; Andreas Handojo; Resmana Lim (Jurnal Infra, 2019)
Indoor Positioning System (IPS) is an alternative method of Global Positioning System (GPS) for navigation and user tracing while inside a building or a closed space. With IPS it’s possible to create a tour guide application for visitors of “Museum Trowulan”, in which the application could give a multimedia information of an item close to the visitor as a user. The calculation method used is trilateration method combined with kalman filter for signal smoothing. Hopefully with this research, there could be a more interactive museum experience.Bluetooth Low Energy (BLE) Beacon is used for IPS to broadcast a signal which could be received by the user via smartphone. User’s position could be calculated from the received signal, and then the nearest item could be shown from calculating each item’s position from user’s position. After calculation the data could be analyzed by museum’s admin.The test results show that the beacon’s position and time used for kalman filter affects the end result of calculation. The smaller the zone created by using 3 beacon, the smaller the error distance of the calculation. The calculation result could be seen through the web application in the form of heatmap and volume chart which is categorized by gender and age. This research could be improved by using noise measurement for kalman filter to improve the accuracy of calculation.